PENERAPAN METODE PEMBELAJARAN THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VA SDN 2 BANDA ACEH - Mira Dahlia Sari; Rapida Wati; Mulyani; Moenti Irfan; Rauza Putri Rinaldi; Rajusandi Rahmat Amin; Julpikar (Guruku)
This Classroom Action Research (PTK) is motivated by the low learning outcomes of students in science subjects, especially this is due to boring teaching methods. This Classroom Action Research (PTK) aims to improve student learning outcomes in Science Class VA SD Negeri 2 Banda Aceh through the application of the Think Pair Share Learning Method. The benefits of this Classroom Action Research (PTK) are that it can improve teacher teaching skills, can improve the quality of teacher teaching, can improve understanding of material for students, can improve and can improve student learning outcomes. Classroom Action Research (PTK) which consists of 2 cycles. The data in this study were obtained from teachers of student test results. Based on the research data from cycle I to cycle II, it is obtained that the level of student learning outcomes has increased significantly. So, the conclusion is that the application of the Think Pair Share Learning Method can improve student learning outcomes in science learning class IV A SD Negeri 2 Banda Aceh.